2017
DOI: 10.1111/apt.13904
|View full text |Cite
|
Sign up to set email alerts
|

The albumin–bilirubin grade improves hepatic reserve estimation post‐sorafenib failure: implications for drug development

Abstract: Abstract.Background: Drug development in hepatocellular carcinoma (HCC) is limited by disease heterogeneity, with hepatic reserve being a major source of variation in survival outcomes. The albumin-bilirubin (ALBI) grade is a validated index of liver function in patients with HCC. Aims:We tested the accuracy of the ALBI grade in predicting post-sorafenib overall survival (PSOS) in patients who permanently discontinued treatment.Methods: From a prospectively maintained international database of 447 consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 34 publications
3
30
0
Order By: Relevance
“…We used the ALBI score as an indicator of liver function. Although we found a significant correlation between Child-Pugh class and ALBI score and several recent studies have reported that ALBI score is a good indicator of liver function, (9)(10)(11)(28)(29)(30)(31) further verification of ALBI score as a measure of liver function is required. When patients were categorized based on tumor markers or liver fibrosis markers, the cut-offs were fixed as the median for each value.…”
Section: Discussionmentioning
confidence: 49%
“…We used the ALBI score as an indicator of liver function. Although we found a significant correlation between Child-Pugh class and ALBI score and several recent studies have reported that ALBI score is a good indicator of liver function, (9)(10)(11)(28)(29)(30)(31) further verification of ALBI score as a measure of liver function is required. When patients were categorized based on tumor markers or liver fibrosis markers, the cut-offs were fixed as the median for each value.…”
Section: Discussionmentioning
confidence: 49%
“…PHLF accidentally occurs in some CP grade A patients as in our study, revealing that the heterogeneity of liver functional reserve may exist in CP grade A patients. Recent studies have shown that dissection of CP grade A by ALBI grade was of great prognostic importance in intermediate or advanced stage of HCC . Our results showed that the CP grade A patients could be successfully reclassified into two subgroups according to ALBI grade and that the incidence of PHLF in the ALBI grade 2 subgroup was higher compared with those with grade 1 ( P =.029).…”
Section: Discussionmentioning
confidence: 51%
“…In the current study, we validated the value of CP score, ALBI score and sFLR in predicting post-operative morbidity and PHLF in [26][27][28] Our results showed that the CP grade A patients could be successfully reclassified into two subgroups according to ALBI grade and that the incidence of PHLF in the ALBI grade 2 subgroup was higher compared with those with grade 1 (P=.029). These data revealed that the ALBI grade served as a useful predictor of PHLF to reclassify CP grade and discriminated those patients with worse liver functional reserve in a CP grade.…”
Section: Discussionmentioning
confidence: 62%
“…Kuo et al suggested not only baseline ALBI grade but its change during treatment could predict the prognosis of HCC under sorafenib treatment. Furthermore, Pinato et al confirmed the ability of ALBI grade at sorafenib discontinuation to select patients for second‐line therapies by identifying their stability of hepatic reserve and survival. These studies have demonstrated the important role of ALBI grade in the survival of HCC undergoing sorafenib treatment; however, the effects of progression pattern and time to progression on PPS were not included.…”
Section: Discussionmentioning
confidence: 97%